Therapeutic Applications of Mesenchymal Stem Cells in Idiopathic Pulmonary Fibrosis - Yang, Shengnan; Liu, Peipei; Jiang, Yale; Wang, Zai; Dai, Huaping; Wang, Chen (Frontiers in Cell and Developmental Biology, 2021)
Idiopathic pulmonary fibrosis (IPF) is an interstitial disease of unknown etiology characterized by progressive pulmonary fibrosis without effective therapy.The pluripotency of mesenchymal stem cells (MSCs) and their ability to regulate immunity, inhibit inflammation, and promote epithelial tissue repair highlight the promise of MSC therapy for treating interstitial lung disease. However, there is a lack of optimal scheme of multi parameter selection in MSC therapy. This review summarizes preclinical studies of MSCs transplantation for the treatment of interstitial lung disease, and clinical studies with known results. An analysis of relevant factors for the optimization of treatment plans is presented, including MSCs from different sources, administration route and time, dosage, frequency, and pretreatment with MSCs. This review proposes an optimized plan for guiding the design of future clinical research in order to identify therapeutic options for this complex disease.